The thymus as a target for mycobacterial infections - Nobrega, Claudia (2007)
Mycobacterial infections are among the major health threats worldwide. Ability to fight these infections depends on the host's immune response, particularly on macrophages and T lymphocytes produced by the thymus. Using the mouse as a model, and two different routes of infection (aerogenic or intravenous), we show that the thymus is consistently colonized by Mycobacterium tuberculosis, Mycobacterium avium or Mycobacterium bovis BCG. When compared to organs such as the liver and spleen, the bacterial load reaches a plateau at later time-points after infection. Moreover, in contrast with organs such as the spleen and the lung no granuloma were found in the thymus of mice infected with M. tuberculosis or M. avium. Since T cell differentiation depends, to a large extent, on the antigens encountered within the thymus, infection of this organ might alter the host's immune response to infection. Therefore, from now on, the thymus should be considered in studies addressing the immune response to mycobacterial infection.